Reading the Soul of Yayat Rukhiyat in Si Rawing: The Spiritual Transformation of a Fictional Character in a Digital Narrative on the Radio Cakra Bandung YouTube Channel - Ucep Hermawan; Dadang Kuswana (Jurnal Iman dan Spiritualitas, 2026)
This study investigates the spiritual transformation of the main character in the Sundanese folktale series Si Rawing, broadcast on the YouTube channel Radio Cakra Bandung. Employing a qualitative content analysis and grounded in James Fowler’s theory of faith development, this research explores how the character’s inner journey reflects a shift from emotional and mythic-literal faith stages to more reflective and universal forms of spiritual awareness. Drawing on a religious psychology approach, the study also examines how the story embodies the lived spiritual experiences of its author, Yayat Rukhiyat. Findings reveal that Si Rawing is not merely a fictional hero but a symbolic projection of the author’s personal struggle with ego, suffering, and the pursuit of inner peace (wening panggalih). The narrative weaves together elements of Sundanese wisdom, Islamic spiritual values, and philosophical reflections into a coherent story of transformation. Moreover, the digital medium of YouTube allows this narrative to transcend local boundaries, making it accessible to a wider audience and reinforcing the role of digital platforms in preserving and transmitting traditional values. By integrating religious psychology, cultural narrative, and digital ethnography, this study offers a novel contribution to the field of digital spirituality and local cultural studies. It demonstrates how fictional narratives can serve as vehicles for both autobiographical reflection and moral-spiritual education, especially within culturally rooted digital spaces.